Penerapan Aplikasi Slims dalam Pelayanan Perpustakaan di SMAN 6 Bone - Sonia Eka Lestari (Institusi Agama Islam Negeri (IAIN) Bone, 2024)
The aim of this research is to determine the application of management information systems in improving the quality of library services at SMAN 6 Bone. The type of research used is qualitative research. Then it is explained descriptively qualitatively. The results of this research indicate that the implementation of the SLIMS application in improving the quality of library services at SMAN 6 Bone is good which can be measured using the PIECES framework which contains six components. First, performance to see to what extent and how reliable an information system is in processing or processing data. Second, the information produced by the system must really have useful value for decision making. Third, economics to see the extent to which the library information system currently being used is commensurate with the results obtained. Fourth, control, namely the aspect of knowing how to control and secure a system. Fifth, efficiency is a reference or guideline used in analyzing and evaluating a system in terms of its efficiency. Sixth, the company's service progress is determined by this variable whether the users are interested and satisfied with the service they have.